Why does the WTO have an Antidumping Agreement? - James C. Hartigan; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
This paper develops a model that offers a plausible interpretation for the empirical observation of diffusion of antidumping (AD) laws amongst WTO members. Contrary to the regnant belief that this proliferation is driven mainly by retaliatory motives, our model shows that adoption and use of AD laws involve a cooperative act amongst WTO members in an infinite horizon game. The diffusion of AD laws need not result in a Prisonner.s dilemma. Instead we show that the AD agreement of the WTO can serve as a risk-sharing vehicle amongst WTO members in response to adverse shocks incurred by domestic producers.
Keywords: F11; F14; F16; 330; Antidumping; non-cooperative games; WTO; proliferation; Antidumping; Außenhandelspolitik; Handelskonflikt; WTO-Regeln; Spieltheorie; Theorie